The Determinants Of Variation Of Population Densities Within Cities Using Normal Micro-Squared LOLS And Geographical Regression GWR Methods - Abdullah, Nashwan Sh. (Academic Journal of Nawroz University, 2017)
Geographical distribution of population inside cities and their affecting factors are the key stone to start arranging the internal structure of the city, the aim of the study is to test the role of these factors ( distance from the city center , size population , area , the rate of height and slope of surface) at the residential quarters level , on the variation of population densities inside the cities of Iraqi Kurdistan Region ( Sulaymaniyah , Erbil , Duhok) and the degree of the effect of each factor and their spatial variation , in accordance with the concept of the Linear Regression Analysis ,using two methods Ordinary Least Squares (OLS) and Geographically Weighted Regression (GWR).. The study revealed the role of three key factors (size population, area, distance from the city center) through high significant statistic, the variation ratio was ranged in between (25-76%) according to the OLS, and (25-83%) according to the GWR. the Impact of the above factors was varied spatially progressively from the city center to the urban margin, as it was expected. In spite of the above mentioned, there was part of variation unexplained, related to the social and economic factors that were not taken in a consideration in this study.